Normativity-Deductivity of Ibn Rusyd’s Bidâyah Al-Mujtahid Wa Nihâyah Al-Muqtashi - Abdul Aziz, Jamal (Institut Agama Islam Negeri Madura, 2016)
Ibn Rusyd, better known as Moslem philosopher, but he was actually an expert in other fields, among which was islamic jurisprudence (fiqh). He wrote a monumental work in the field of Islamic jurisprudence, namely the Bidâyah al-Mujtahid wa Nihâyah al-Muqtashid. This book compiles the book systematically, logical, and comprehensive, and serves a variety of opinions from various schools of jurisprudence that developed at that time objectively. This paper examines about Muqaddimah Bidâyah Kitab al-Mujtahid that comprise theories of understanding religious text (al-adillah al-shar’îyah) underlying causes of dissent which will be described in it, also on the systematization of this book. I finally concludes that the book Bidâyah al-Mujtahid wa Nihâyah al-Muqtashid is fiqh comparison described systematically-logical-argumentative and contains themes of fiqh holistically-comprehensive.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i1.1000